2019
DOI: 10.5312/wjo.v10.i9.327
|View full text |Cite
|
Sign up to set email alerts
|

Who should you be following? The top 100 social media influencers in orthopaedic surgery

Abstract: BACKGROUNDSocial media has been credited with the potential to transform medicine, and Twitter was recently named “an essential tool” for the academic surgeon. Despite this, peer-to-peer and educational influence on social media has not been studied within orthopaedic surgery. This knowledge is important to identify who is controlling the conversation about orthopaedics to the public. We hypothesized that the plurality of top influencers would be sports medicine surgeons, that social media influence would not … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
66
1
7

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(79 citation statements)
references
References 31 publications
3
66
1
7
Order By: Relevance
“…The role of social media platforms in orthopaedic research has expanded in recent years. Both patients and surgeons increasingly look to social media platforms such as Twitter to communicate, educate, and disseminate information, 1 2 3 4 5 6 and many academic journals have adopted Twitter profiles in response. 7 , 8 In this study, through a systematic analysis of recent research publications in three high-impact orthopaedic surgery journals, we have shown that social media posting is weakly, but markedly, correlated with academic citation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The role of social media platforms in orthopaedic research has expanded in recent years. Both patients and surgeons increasingly look to social media platforms such as Twitter to communicate, educate, and disseminate information, 1 2 3 4 5 6 and many academic journals have adopted Twitter profiles in response. 7 , 8 In this study, through a systematic analysis of recent research publications in three high-impact orthopaedic surgery journals, we have shown that social media posting is weakly, but markedly, correlated with academic citation.…”
Section: Discussionmentioning
confidence: 99%
“…The use of social networking and microblogging platforms for novel information in orthopaedic surgery has risen in recent years among patients and physicians alike. 1 2 3 4 5 6 Web-based social media platforms are increasingly used to share and disseminate original scientific research. Many academic journals have adopted Twitter profiles to have a greater social media presence, both within the academic community and the general public.…”
mentioning
confidence: 99%
“…This includes posting frequently, following related accounts and re-posting content, and using hashtags. 17,21,37 There are also social media marketing strategies of identifying a target audience, staying active, and having discussions with other accounts on relevant topics. 38 Programs already using hashtags should continue utilization to maintain their existing audience.…”
Section: Discussionmentioning
confidence: 99%
“…Social media has become a leading forum for discourse, connecting to 2 billion Facebook users, 500 million Twitter users, 2 billion daily YouTube viewers, and 600 million Instagram accounts. 3,7,10,22 Users rely on the platforms to disseminate health care information and as source of referrals, 15,20,27 and in response, physicians have amplified their online presence in this rapidly changing medium. 16 Recent studies show that 80% of patients use the Internet for health care questions and 90% of physicians use a social media platform.…”
Section: Introductionmentioning
confidence: 99%